Assessing the Mediating Role of Work Engagement Between the Relationship of Corporate Social Responsibility with Job Satisfaction and Organizational Citizenship Behavior - Ali, Muhammad; Ali, Fouzia Hadi; Raza, Basharat; Ali, Wasif (International Review of Management and Marketing, 2020)
This study investigates how perceived corporate social responsibility directly influence the job satisfaction and organizational citizenship behavior of employees, and indirectly influence through the mediating effect work engagement. A questionnaire-based survey was conducted to collect data from 327 students of MBA executive employed in different organizations of Lahore, Pakistan. Structural equation modeling was applied to test the hypothesized conceptual model. Results reveal that corporate social responsibility activities of the organizations increase job satisfaction and discretionary behaviors or organizational citizenship behavior among employees. CSR also increases work engagement, which, in turn, increases job satisfaction and organizational citizenship behavior as well. This study has shown that concerns toward CSR have increased in the business organization operating in developing countries, and employees working in those organizations are reciprocating to CSR through positive outcomes in the workplace. The employees, as internal stakeholders are responding favorably to the CSR. As per the best of researchers’ knowledge, the study firstly tests the mediating role of work engagement in the linkage of CSR with job satisfaction and organizational citizenship behavior. The theoretical and practical implications are also discussed. Keywords: Corporate social responsibility, Job satisfaction, Organizational citizenship behavior, Work engagement JEL Classifications: M14, J24, J28 DOI: https://doi.org/10.32479/irmm.9714